Development of a Digital Hologram Map Using Bathymetric Data - Jumamurod Farhod Ugli Aralov; Oybek Mirzaevich Narzulloev; Leehwan Hwang; Philippe Gentet; Seunghyun Lee (IEEE Access, 2025)
This study examines the development of hologram maps that provide a precise, intuitive depiction of underwater topography in a genuine three-dimensional format. It integrates sophisticated holographic methodologies with bathymetric datasets to address the challenges of visualizing intricate marine environments. Most traditional bathymetric mapping techniques rely on two-dimensional representations, which require users to mentally infer depth and spatial relationships. This cognitive burden can lead to misinterpretation, particularly when analyzing complex seafloor structures with subtle variations. Data from the General Bathymetric Chart of the Oceans was used to construct and enhance three-dimensional terrain models within Blender. Holographic representations were generated utilizing the Digital Holographic Stereogram Printing method, which produced two holograms representing the underwater morphology of Monterey Canyon and its terrestrial features. These holograms enhance accuracy and depth perception, fostering a deeper understanding of the canyon’s geological complexities. This pioneering methodology provides a robust technique for scientific studies and suggests novel approaches for public engagement and educational outreach. By integrating bathymetric data with holographic visualization, this study highlights the importance of precise and accessible three-dimensional mapping in advancing oceanographic research, enhancing underwater analysis, and supporting marine science.